Controversy over Corruption Inmate Release in the Midst of the Covid-19 Pandemic - Sihotang, Natalia (The Indonesian Journal of International Clinical Legal Education, 2020)
Discourse on the release of prisoners in order to reduce the rate of transmission of the corona virus (Covid-19) is still a polemic. The policy is considered by some to be able to cause new problems, namely increasing crime rates. One such policy is to accelerate the release of prisoners and children through the crash of the integration rights program that has been running since last year. The basis is indeed stipulated in the Regulation of the Minister of Law and Human Rights No. 10 of 2020, Decree of the Minister of Law and Human Rights No.M.HH- 19 PK.01.04.04 Year 2020, and Director General of Corrections Circular Letter Number: PAS-497.PK.01.04.04 Year 2020.